Вплив способу основного обробітку ґрунту на формування врожайності зерна кукурудзи - Якунін, Олексій Панасович; Yakunin, Oleksiy; Храмцов, Л. І.; Hramtsov, L.; Трубілов, Олег Віталійович; Trubilov, Oleg (Дніпровський державний аграрно-економічний університет, 2015)
Викладено результати досліджень щодо впливу способу та глибини основного обробітку ґрунту на формування зернової продуктивності кукурудзи. Заміна оранки на 25–27 см спушуванням ґрунту на таку саму глибину позитивно впливало на рівень забур’яненості посівів, запасів доступної вологи в ґрунті, врожайності зерна і на економічну ефективність його вирощування. Встановлено погіршення цих показників у варіантах дискування на 12–14 см і нульового обробітку. The features of grain productivity formation of early-ripening corn hybrid Dneprovskyi 181 SV are determined depending on the methods of the basic soil tillage in three-year researches, conducted in the conditions of Zaporozhye region.The quantities of weeds, their weight were as the least in a variant of soil loosening with deep-ripper on the depth 25–27 cm. These indicators were as the most by discing on the cm depth 12–14. The replacement of ploughing with depth 25–27 cm (control or nontreated variant) on the loosening with the same depth provided with the increase of available moisture stocks in a layer of soil 0–100 cm at corn sowing – on 16 mm and in a phase of maize tasseling – on 8 mm. By discing of soil with depth 12–14 cm and no-tillage the available moisture stocks was decreased for 6–8 mm.The grain productivity was on 0,25 tonn/hectare more on the background of deep loosening of soil (depth 25–27 cm) in comparison with the control (ploughing with depth 25–27 cm). On this variant there were obtained the best economic effectiveness indicators – the conditional net income and the level of profitability. At replacement of ploughing by discing on depth 16–18 cm and 12–14 cm the grain productivity was decreased in comparison with the control (ploughing with depth 25–27 cm) accordingly for 0,43 and 0,66 tonn/hectare, and by no-tillage – on 0,89 tonn/hectare. In comparison with ploughing the conditional net income by discing on depth 16–18 cm decreased for 598 UAH/hectare, by discing on depth 12–14 cm and by no-tillage – accordingly on 931 and 1236 UAH/hectare.
Influence of the basic soil tillage means on the formation of corn grain productivity
Keywords: кукурудза; corn; обробіток ґрунту; soil tillage; бур’яни; weeds; ґрунтова волога; soil moisture; врожайність зерна; grain productivity; економічна ефективність; economic efficiency